Protein domain-dependent vesiculation of Lipoprotein A, a protein that is important in cell wall synthesis and fitness of the human respiratory pathogen Haemophilus influenzae - Jalalvand, Farshid; Su, Yu-Ching; Manat, Guillaume; Chernobrovkin, Alexey; Kadari, Mahendar; Jonsson, Sandra; Janousková, Martina; Rutishauser, Dorothea; Semsey, Szabolcs; Løbner-Olesen, Anders; Sandblad, Linda; Flärdh, Klas; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
The human pathogen Haemophilus influenzae causes respiratory tract infections and is commonly associated with prolonged carriage in patients with chronic obstructive pulmonary disease. Production of outer membrane vesicles (OMVs) is a ubiquitous phenomenon observed in Gram-negative bacteria including H. influenzae. OMVs play an important role in various interactions with the human host; from neutralization of antibodies and complement activation to spread of antimicrobial resistance. Upon vesiculation certain proteins are sorted and mainly found in OMVs, and the mechanism for this phenomenon is not fully clear. We employed mass spectrometry to study vesiculation and the fate of proteins in the outer membrane. Functional groups of proteins were differentially distributed on the cell surface and in OMVs. Despite its supposedly periplasmic and outer membrane location, we found that the peptidoglycan synthase-activator Lipoprotein A (LpoA) was accumulated in OMVs relative to membrane fractions. A mutant devoid of LpoA lost its fitness as revealed by growth and electron microscopy. Furthermore, high-pressure liquid chromatography disclosed a lower concentration (55%) of peptidoglycan in the LpoA-deficient H. influenzae compared to the parent wild type bacterium. Using an LpoA-mNeonGreen fusion protein and fluorescence microscopy, we observed that LpoA was enriched in “foci” in the cell envelope membrane, and further located in the septum during cell division. To define the fate of LpoA, C-terminally truncated LpoA-variants were constructed, and we found that the LpoA C-terminal domain promoted optimal transportation to the OMVs as revealed by flow cytometry. Taken together, our study highlights the importance of LpoA for H. influenzae peptidoglycan biogenesis and provides novel insights into cell wall integrity and OMV production.